Ecology of mycotoxin producing fungi present in wine grapes - Serra, Rita (2003)
In order to establish the potencial mycotoxin producer species hazardous for wine quality, surveys of filamentokis fungi were made in Portuguese wine grapes. These studies were conducted from 1999 to 2002, and are still ongoing. Among the more relevant fungi detected in grapes are black aspergilli, namely A. niger aggregate and A. carbo;arius, found to be responsible for the production of ochratoxin A in grapes. The results of these studies are discussed in an ecological point of view, and in terms of risk assessment for mycotoxins presence in the final product, wine.